Development of Nearpod-Based Interactive Media to Optimize Religious Moderation - Adistya, Ananda Feby; Yulia, Nurul Mahruzah; Amreta, Midya Yuli; Musthofa, Muhammad Yunus (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
The problem often faced by the world of education is students' attitudes towards learning. In fact, students easily get bored with learning that only uses textbooks in the form of worksheets in class. Students are more enthusiastic about smartphones than live games. Students also often show a lack of tolerance in learning. This research aims to describe the development process and results of developing interactive media on religious diversity in Indonesia based on Nearpod. Researchers used the Research and Development method with the ADDIE research model. This media has been validated by media experts with results of 88%, material experts with results of 90%, and learning experts with results of 82%. This media was tested on class IV students at Islamic Elementary School Fathul Ulum Sukosewu. The effectiveness of the media used is 0.61, which means that Nearpod-based interactive media is quite effective in optimizing religious moderation at Islamic Elementary School Fathul Ulum Sukosewu. Apart from that, with this media students can also better understand and understand other people's opinions.Â Permasalahan yang sering dihadapi dunia pendidikan adalah sikap siswa dalam pembelajaran. Bahkan, siswa gampang merasa bosan dengan pembelajaran yang hanya menggunakan buku ajar berupa LKS di kelas. Siswa lebih antusias dengan smartphone dari permainan langsung. Lemahnya sikap toleransi juga sering ditunjukkan siswa dalam pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan proses pengembangan dan hasil pengembangan media interaktif materi keberagaman agama di Indonesia berbasis Nearpod. Peneliti menggunakan metode Research and Development (RND) dengan model penelitian ADDIE. Hasil penelitian menjelaskan bahwa Prosedur pengembangan media interaktif berbasis Nearpod ini menggunakan model pengembangan ADDIE yang terdiri dari lima langkah yaitu analysis, design, development, implementation, evaluation. Media ini telah di validasikan oleh ahli media dengan hasil 88%, ahli materi dengan hasil 90%, dan ahli pembelajaran dengan hasil 82%. Media ini di uji cobakan kepada siswa siswi kelas IV Madrasah Ibtidaiyah Fathul Ulum Sukosewu. Efektivitas media yang digunakan yaitu sebesar 0,61 yang berarti media interaktif berbasis Nearpod ini cukup efektif untuk mengoptimalkan moderasi beragama di Madrasah Ibtidaiyah Fathul Ulum Sukosewu. Selain itu, dengan media ini siswa juga dapat lebih mengerti dan memahami pendapat orang lain.